Perancangan Simulasi Saklar Otomatis Menggunakan Sensor PIR Berbasis Arduino Berdasarkan Pergerakan Manusia - Umar Faruq Al-afifi; Erdin Syam; Ibrahim Bahar; Elvin Piter (Universitas Muhammadiyah Purwokerto, 2021)
In the digital era and technology today is still often found lack of awareness in the application of a system can cause severe fatality both workplace accidents and energy waste. In an effort to overcome the problem in the form of energy waste, a number of discoveries were made to create a tool that can be a solution to the problem, the tool is categorized in Instrumentation. In the example of the case of using electrical energy in a room, it is often found that electrical energy is wasted because of negligence to turn off when not in use, cases like this give birth to countermeasures innovation that is an automatic switch system that uses the PIR Sensor as a detection. This journal will explain how systematic the innovation is, and to make it easier, it will be visualized based on simulations using the Proteus application. This innovation provides a solution in the form of a comparison of energy usage with the case of using a 12Watt lamp load when without using a device which means 24 hour usage ± 0.288 kwH / Day and when using a tool that is ± 0.072 kwH / Day it can be even lower depending on the intensity of lamp usage in a day . With this data shows that this tool can provide significant energy efficiency, and certainly can save electricity bills when applied.